Elastoplastic Analysis of Circular Tunnel Based on Drucker–Prager Criterion - Xiongfei Yang; Hong Yuan; Jiayu Wu; Shanqing Li (Advances in Civil Engineering)
Based on the Drucker–Prager yield criterion, the theoretical solution of stratigraphic deformation in tunnel excavation process is deduced by the cavity expansion theory. In view of soil loosening around the tunnel caused by the tunnel excavation process, the internal friction angle of the surrounding soil is not a constant but a function of normal stress. The piecewise linearization of the nonlinear yield function is used to analyze the elastoplastic solution of the cylindrical hole shrinkage. A comparison is conducted with a plastic zone in which the internal friction angle of the soil remains unchanged. It can be concluded that the radial stress, the tangential stress, the radial strain, and the tangential strain around the inner wall calculated from the former are smaller.